2014
DOI: 10.1002/psc.2620
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of oxidized peptide fragments of the C-terminal redox center in thioredoxin reductases by NMR spectroscopy

Abstract: Vicinal disulfide rings (VDRs) occur when a disulfide bond forms between adjacent cysteine residues in a protein and results in a rare eight-membered ring structure. This eight-membered ring has been found to exist in four major conformations in solution, divided between cis and trans conformers. Some selenoenzymes use a special type of VDR in which selenium replaces sulfur, generating a vicinal selenosulfide ring (VSeSR). Here we provide evidence that this substitution reduces ring strain, resulting in a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…A possible explanation as to why Kb TrxR can reduce GSSG while mammalian TrxR cannot is that Kb TrxR may bind GSSG similarly to the way in which glutathione reductase (GR) does. When bound to GR, GSSG is in a highly strained conformation, which facilitates GSSG reduction . TrxR and GR are evolutionarily and structurally related, with both having a conserved N-terminal CVNVGC redox center and a bound flavin .…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation as to why Kb TrxR can reduce GSSG while mammalian TrxR cannot is that Kb TrxR may bind GSSG similarly to the way in which glutathione reductase (GR) does. When bound to GR, GSSG is in a highly strained conformation, which facilitates GSSG reduction . TrxR and GR are evolutionarily and structurally related, with both having a conserved N-terminal CVNVGC redox center and a bound flavin .…”
Section: Resultsmentioning
confidence: 99%
“…The 14‐membered rings of oxidized CXXC cyclic peptides have wider variation in available conformations than the smaller CC/U motif . In multi‐μs MD simulations, CGGC has multiple regions of varying root mean square (RMSD) (Figure ) indicating a high degree of ring flexibility.…”
Section: Resultsmentioning
confidence: 99%
“…Conformations of the CC(U) ring, having the most ring strain and the least number of available conformations have been studied extensively. [31][32][33][34] Density functional theory (DFT) calculations showed that the observed 77 Se NMR spectrum of the CU motif was consistent with multiple conformations of the eight-membered ring coexisting in solution rather than different selenium functionalities or oxidation states. 35,36 In larger, more flexible cyclic CXXC(U) motifs, various groups have used molecular modeling to explore the conformation space of the oxidized peptides.…”
mentioning
confidence: 87%
See 2 more Smart Citations